PENGARUH RENTABILITAS, DAN LEVERAGE PADA SAHAM BONUS DI PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Surya Wibawa, I.B. Oka; Astika, I.B. Putra (E-Jurnal Akuntansi, 2016)
This study aims to determine the effect of profitability (ROA) and leverage (DER) in bonus shares. This research was conducted in all companies listed on the Indonesia Stock Exchange 2000-2014 period. The sample was 45 companies. The sample in this research is determined by purposive sampling method. The data analysis technique used is multiple linear regression analysis. Based on the results of the study showed that profitability does not affect the bonus shares. This shows the company's decision to take the bonus shares policy does not depend on the size of profitability, and if profitability is high then the company 'companies tend to distribute dividends in cash. Leverage positive effect on bonus shares. This shows that the greater the risk of the company, the company management does not tend to distribute dividends in cash, but the bonus shares.
Keywords: bonus shares, rentability, leverage